Design, synthesis of new β-carboline derivatives and their selective anti-HIV-2 activity. Issue 6 (15th March 2015) - Ashok, Penta; Chander, Subhash; Balzarini, Jan; Pannecouque, Christophe; Murugesan, Sankaranarayanan
Graphical abstract: Abstract: In the present study, a new series of β-carboline derivatives were synthesized and evaluated for inhibition activity against both HIV-1 and HIV-2 strains. Among these reported analogues, surprisingly (1-phenyl-9 H -pyrido[3, 4- b ]indol-3-yl)(4- p -tolylpiperazin-1-yl)methanone (7b ), (4-(2-methoxyphenyl)piperazin-1-yl)(1-phenyl-9 H -pyrido[3, 4- b ]indol-3-yl)methanone (7f ), (4-(4-fluorophenyl)piperazin-1-yl)(1-phenyl-9 H -pyrido[3, 4- b ]indol-3-yl)methanone (7k ), (4-(2-fluorophenyl)piperazin-1-yl)(1-phenyl-9 H -pyrido[3, 4- b ]indol-3-yl)methanone (7l ) displayed selective inhibition of HIV-2 strain with EC50 values of 3.3, 3.2, 2.6 and 5.4 μM, respectively, which are comparable with nucleoside reverse transcriptase inhibitors lamivudine and dideoxyinosine. As these analogues have not shown in vitro HIV-2 reverse transcriptase inhibition, it could be excluded as potential target for their specific anti-HIV-2 activity.